Long‐Term Changes of Sexual Function in Men with Obstructive Sleep Apnea after Initiation of Continuous Positive Airway Pressure. (22nd October 2012) - Budweiser, Stephan; Luigart, Ruth; Jörres, Rudolf A.; Kollert, Florian; Kleemann, Yannick; Wieland, Wolf F.; Pfeifer, Michael; Arzt, Michael
ABSTRACT Introduction. Obstructive sleep apnea (OSA), particularly intermittent nocturnal hypoxemia, is associated with erectile dysfunction (ED). Aim. We investigated in patients with OSA whether continuous positive airway pressure (CPAP) therapy has a long‐term effect on sexual function, including ED, in the presence of other risk factors for ED. Methods. Within a long‐term observational design, we reassessed 401 male patients who had been referred for polysomnography, with respect to erectile and overall sexual function. Mean ± standard deviation follow‐up time was 36.5 ± 3.7 months. Patients with moderate to severe ED were stratified according to the regular use of CPAP. Main Outcome Measure. Changes of sexual function were assessed by the 15‐item International Index of Erectile Function (IIEF‐15) questionnaire, including the domains erectile function (EF), intercourse satisfaction, orgasmic function (OF), sexual desire (SD), and overall satisfaction (OS). Results. Of the 401 patients, 91 returned a valid IIEF‐15 questionnaire at follow‐up. Their baseline characteristics were not different from those of the total study group. OSA (apnea–hypopnea index >5/hour) had been diagnosed in 91.2% of patients. In patients with moderate to severe ED (EF domain <17), CPAP users (N = 21) experienced an improvement in overall sexual function (IIEF‐15 summary score; P = 0.014) compared with CPAP non‐users (N = 18), as well as in the subdomains OF (P = 0.012), SD (P = 0.007), and OS (P = 0.033). Similar results were obtained in patients with poor overall sexual dysfunction (IIEF‐15 summary score <44). In patients with moderate to severe ED and low mean nocturnal oxygen saturation (≤93%, median), also the EF subdomain improved in CPAP users vs. non‐users (P = 0.047). Conclusions. These data indicate that long‐term CPAP treatment of OSA and the related intermittent hypoxia can improve or preserve sexual function in men with OSA and moderate to severe erectile or sexual dysfunction, suggesting a certain reversibility of OSA‐induced sexual dysfunctions. Budweiser S, Luigart R, Jörres RA, Kollert F, Kleemann Y, Wieland WF, Pfeifer M, and Arzt M. Long‐term changes of sexual function in men with obstructive sleep apnea after initiation of continuous positive airway pressure. J Sex Med **;**:**–**.